Pengaruh Belajar Tipe Teams Games Tournament (TGT) Terhadap Hasil Belajar Matematika - Anas Taufiqurrahman; Andes Safarandes Asmara (LPPM Universitas Buana Perjungan Karawang, 2020)
This study aims to determine the effect of the Teams Games Tournament (TGT) type of cooperative learning methods on mathematics learning outcomes at Adiarsa Barat II Elementary School, West Karawang District, Karawang District. This research is a type of quantitative research. The population in this study were grade II students of Adiarsa Barat II Elementary School. The sample in this study amounted to 22. The technique of collecting data through filling tests with Mathematics subjects. Researchers use data analysis techniques, namely statistical calculations. The results of hypothesis testing, there are significant differences between the cooperative learning methods of Teams Games Tournament (TGT) and Mathematics learning outcomes. This was obtained (tcount = 5.813> t table = 2.085) with a significance of 0.05 and n = 22 indicating that the hypothesis was accepted. From the results of this study it can be said there are differences in learning outcomes in Mathematics with cooperative learning methods of the Teams Games Tournament (TGT) type